Preliminary evidence of antitumour activity of Ipatasertib (Ipat) and Atezolizumab (ATZ) in glioblastoma patients (pts) with PTEN loss from the Phase 1 Ice-CAP trial (NCT03673787). (15th October 2021) - Tiu, Crescens; Welsh, Liam; Jones, Timothy; Zachariou, Anna; Prout, Toby; Turner, Alison; Daly, Rob; Tunariu, Nina; Riisnaes, Ruth; Gurel, Bora; Crespo, Mateus; Carreira, Suzanne; et al.
Abstract: Aims: Despite improved understanding of effector T-cell trafficking into the central nervous system, initial trials with anti-PD1/PD-L1 immune checkpoint inhibitors (ICIs) have failed to meet their primary endpoints. PTEN loss of function is frequent in GBM and has been correlated with not only poor overall prognosis, but also impaired antitumour responses, including reduced T cell infiltration into tumour and reduced efficacy of ICIs. Ipatasertib is a novel, potent, selective, small-molecule inhibitor of Akt. We have shown that Ipatasertib efficiently depletes FOXP3+ regulatory T cells from the tumour microenvironment (TME) resulting in increased infiltration of effector T cells in solid tumours (Lopez 2020, AACR). We hypothesize that the use of AKT inhibition in PTEN glioblastomas may deplete the TME of suppressive immune cells, and render malignant brain tumours more responsive to ICIs. We present updated data for the combination of Ipat+ATZ in patients with glioblastoma. Method: Patients with relapsed WHO grade IV GBM with stable neurological symptoms ≥5 days prior to enrolment, requiring <3mg Dexamethasone were recruited into two cohorts of this early phase, open-label, single-centre trial studying the combination of Ipatasertib (Ipat) and Atezolizumab (ATZ): a dose finding cohort (A2; n=9) and an expansion cohort (B3; n=7, recruitment ongoing). The Ice-CAP A2 cohort assessed safety, pharmacodynamic, and preliminary clinical activity of Ipat (200mg or 400mg OD) + ATZ (1200mg Q3W) in pts with potentially resectable relapsed WHO Grade IV GBM. Pts had a 14-21-day run-in phase of Ipat then surgical tumour resection. Combination Ipat+ATZ commenced post surgery. Patients who declined surgery or who were deemed high risk for surgery proceeded directly to combination. Patients in the expansion cohort B3 commenced directly on Ipat+ATZ at the RP2D of 400mg Ipat with ATZ. Results: 16 evaluable recurrent GBM pts were enrolled across two cohorts. Median age 56 yrs (25-71 yrs). Median ECOG PS 1. Median lines of prior therapy 1 (range 1-4). 10 pts had PTEN loss by IHC (H<30) and/or PTEN mutations on next generation sequencing. No DLTs, treatment-related (TR) serious adverse events (AEs), or immune-related AEs were observed. Most common TR AEs were G1 diarrhoea (44%), mucositis (17%), rash (28%). Clinical benefit rate (CR, PR and SD> 6 cycles) at clinical cutoff date (23/02/21) in patients with PTEN aberration was 30% (3/10). A 58-year-old man with PTEN loss had MRI at Cycle 5 showing worsening enhancement suggestive of disease progression. Resection of the lesion showed intense lymphocyte infiltration and pathological CR. He is currently on Cycle 22 with no evidence of disease. Two other patients with PTEN loss with radiological stable disease per RANO criteria remain well on study for >6 cycles. Conclusion: Combination Ipat+ATZ appears safe and tolerable in GBM pts, with 400mg Ipatasertib OD + 1200mg ATZ Q3W declared as RP2D. Early efficacy signals were detected with PTEN loss being a promising predictive biomarker for response to combination. An expansion cohort enriched with pts with PTEN loss is ongoing.